Pengembangan Permainan Papan Kampung Pancasila Sebagai Media Pembelajaran Dalam Memperkuat Profil Siswa Pancasila Di SMPIT LHI - Nofiati, Siti; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to develop learning media that can strengthen the profile of Pancasila students. This type of research is Research and Development with the ADDIE development model developed by Dick and Carry. The stages of the development of this research, namely the researcher conducted an analysis of student learning needs (Analysis), then designed the media and materials to be compiled (Design). Researchers developed instructional media based on the results of an analysis of students' learning needs and the design of materials that had been developed (Development). Then the researcher implements the learning media that has been developed in the form of Kampung Pancasila board games (Implementation), and at the end of the stage the researcher evaluates the learning media (Evaluation). The development of this media has gone through several validation stages, namely validation from material experts and validation from media experts. The instruments used in collecting research data consisted of validity testing instruments in the form of expert validation sheets, questionnaires to determine the feasibility of the media and observation sheets to determine the effectiveness of the implementation of activities. Data analysis in this study used descriptive statistics. The results showed that Kampung Pancasila board game could be used as a learning media in strengthening Pancasila students. Kampung Pancasila board game has a high feasibility value as a learning media in strengthening Pancasila students. Kampung Pancasila board game is considered an interesting learning media, making it easier for students to understand material regarding Pancasila student profiles and being able to improve students' abilities in solving social problems.